DanfeNER - Named Entity Recognition in Nepali Tweets - Nobal Niraula; Jeevan Chapagain (Proceedings of the International Florida Artificial Intelligence Research Society Conference, 2023)
Twitter allows users to easily post tweets on any subject or event anytime, generating massive amounts of rich text content on diverse topics. Automated methods such as Named Entity Recognition (NER) are required to process the massive tweet data. Processing tweets, however, poses a special challenge as they are informal posts with incomplete context and often contain acronyms, hashtags, misspellings, abbreviations, and URLs due to length constraints. This paper presents the first systematic study of NER in Nepali tweets corresponding to five different entity types: Person Name (PER), Location (LOC), Organization (ORG), Date (DAT), and Event (EVT). We develop DanfeNER, the first human-labeled high-quality NER benchmark data sets for the low-resource language Nepali. DanfeNER contains 5,366 records and 3,463 entities in its train set and 2,301 records and 1,503 entities in its test set. Using this data set, we benchmark several state-of-the-art Nepali monolingual and multilingual transformer models, obtaining micro-averaged F1 scores up to 81%.